Factors affecting firm’s propensity to pay dividends: Evidence from Vietnam’s listed companies - Nguyen, Do Quyen; Bui, Quang Huy (Journal of International Economics and Management, 2016)
Focusing on non-financial listed firms on Ho Chi Minh Stock Exchange of Vietnam, we examine factors that affects firms’ propensity to pay dividends during 2009-2015. Our results suggest that small firms incline towards dividends as a signal of good performance to investors to raise more equity. In addition, dividend policies are not stable over time and the smoothing effect dividend policies are less apparent. Moreover, foreign investors have little power in monitoring managers so they use dividend as a tool to control for the agency problems and mitigate free cash flow problem. Overall, the agency theory, signaling theory and life cycle hypothesis are found to help explain main factors affecting firms’ dividend policies.